American icon [compact disc, unabridged] : Alan Mulally and the fight to save Ford Motor Company - Hoffman, Bryce G. (Tantor Media, 2012)
A riveting, behind-the-scenes account of the near collapse of the Ford Motor Company, which in 2008 was close to bankruptcy, and CEO Alan Mulally's hard-fought effort and bold plan, including his decision not to take federal bailout money, to bring Ford back from the brink.